TINJAUAN YURIDIS EKSEKUSI PEMBEBASAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM - Dody W. Leonard Silalahi; Nabitatus Sa’adah (Trunojoyo Madura University, 2023)
This study aims to determine the legal basis of the land acquisition process and mechanism, as well as to find out the obstacles that occur in the mechanism of land acquisition for the public interest. In practice, that the need for land will in turn have an impact on various land use issues, land affairs are not only related to socio-economic aspects, but are also related to juridical issues. Because in an effort to use land, it is necessary to provide a guarantee of legal certainty. This research is important in order to be able to overcome the problems regarding land acquisition for public interest in Indonesia. This research method is normative juridical. The results of the study concluded that in carrying out land acquisition referring to Law no. 2 of 2012 concerning Land Procurement for Development in the Public Interest which consists of the planning, preparation, implementation and delivery of results. In addition, the details of the implementation and process are regulated in Presidential Regulation no. 148 of 2015 which updated Presidential Regulation No. 71 of 2012 concerning the Implementation of Land Procurement for Development in the Public Interest.